Variations of the Escherichia coli population in the digestive tract of broilers. Issue 6 (1st November 2020) - Mourand, Gwenaëlle; Le Devendec, Laëtitia; Delannoy, Sabine; Fach, Patrick; Keita, Alassane; Amelot, Michel; Jaunet, Hervé; Dia, Mohamed El Hassimiou; Kempf, Isabelle
ABSTRACT: We explored the between-group and temporal variations in the intestinal Escherichia coli populations of broilers under experimental conditions, taking both antimicrobial resistance and virulence into consideration. Four replicates of 45 commercial chicks were reared in four animal facilities. On their first day of life (Day 0), they were orally inoculated with two extended-spectrum-cephalosporin-resistant (ESCR) E. coli (2.72 log10 CFU of a bla CMY-2- and 2.55 log10 CFU of a bla CTX-M- carrying E. coli ). Faecal samples were then collected weekly and caecal samples were obtained from birds sacrificed on Days 21 or 42. The total, ESC-, ciprofloxacin- and gentamicin-resistant E. coli populations were enumerated on MacConkey (MC) and MC-supplemented media, and eight virulence-associated genes (VAGs) ( iroN, iutA, iss, ompT, hlyF, vat, frzorf4, and fyuA ) were sought by PCR on isolates obtained on MC agar. The results showed significant between-group differences in the size of the resistant sub-populations and the presence of VAGs. Contrary to bla CTX-M -positive strains, bla CMY -positive strains persisted up to Day 42, but represented only a minor fraction of the total E. coli population. The ESC-, gentamicin- and ciprofloxacin-resistant populations decreased over time. Isolates obtained during the first week contained a mean of 5.1 VAGs. The percentages of some VAG profiles differed between faecal isolates on Day 41 and caecal isolates on Day 42. The fluctuations or differences between E. coli isolates according to group, age, and faecal or caecal origin need to be considered when designing experimental protocols and seeking to improve colibacillosis control. RESEARCH HIGHLIGHTS Temporal variations in the intestinal E. coli populations of broilers was studied. The antibiotic-resistant populations decreased over time. Virulence profiles differed between faecal isolates on Day 41 and caecal isolates on Day 42. Strains with the highest numbers of virulence genes were present during the first days.